TYRE 5.0 : Advancement towards economical driving and saving lives - Subramonian, Sivarao (Penerbit UTeM Press, 2023)
This book explores the vital link between tyre pressure, safety, and driving economy, inspired by the author’s personal experience with tyre-related accidents. Based on research at Universiti Teknikal Malaysia Melaka (UTeM) since 2004, it presents innovative solutions to maintain proper tyre pressure, including mechanical systems, bio-based nanotechnology, and a modular airless tyre. These developments, aligned with UTeM’s Tyre Research Roadmap (2004–2020), aim to enhance road safety and promote economical, sustainable driving.